1990
DOI: 10.1002/tea.3660270906
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in teacher‐student interactions in science classrooms

Abstract: Thirty physical science and 30 chemistry.classes, which contained a total of 1332 students, were observed using the Brophy-Good Teacher-Child Dyadic Interaction System. Classroom interactions were examined for gender differences that may contribute to the undempresentation of women in physics and engineering courses and subsequent careers. The Brophy-Good coding process allows for examination of patterns of interactions for individuals and groups of pupils. An analysis of variance of the data yielded a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
1
8

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(102 citation statements)
references
References 17 publications
9
81
1
8
Order By: Relevance
“…The sixth grade boys' "non-text" and their third marker, aural comprehension, fit with the research: 1) boys receive more interaction from the teacher (Jones & Wheatley, 1990;Parsons,Kaezala, & Meece,1982;Simpson & Erikson, 1983;) rather than the text; 2) boys feel more independent (Grieb & Easley, 1984;Kimball, 1989), and hence may not be as concerned with the text and the teachers' structuring instruction around the text; 3) boys are not as good readers (Feingold, 1993;Leinhardt, Seewald, & Engel, 1979) and thus may prefer to listen; 4) boys tend to be better listeners (Brimer, 1969).…”
Section: -14supporting
confidence: 66%
“…The sixth grade boys' "non-text" and their third marker, aural comprehension, fit with the research: 1) boys receive more interaction from the teacher (Jones & Wheatley, 1990;Parsons,Kaezala, & Meece,1982;Simpson & Erikson, 1983;) rather than the text; 2) boys feel more independent (Grieb & Easley, 1984;Kimball, 1989), and hence may not be as concerned with the text and the teachers' structuring instruction around the text; 3) boys are not as good readers (Feingold, 1993;Leinhardt, Seewald, & Engel, 1979) and thus may prefer to listen; 4) boys tend to be better listeners (Brimer, 1969).…”
Section: -14supporting
confidence: 66%
“…To cite an illuminating facet, studies have shown that teachers judge as well as respond differently to performance outputs by boys and girls during class (cf. Jones and Wheatley 1990;Tiedemann 2002). In this sense, the award ceremony and differential treatment of our subjects just mimics fundamental aspects of social reality.…”
Section: Discussionmentioning
confidence: 97%
“…Male teachers also had significantly higher ratings for using IWBs to increase interactions between teachers and students. Gender differences have been found in teacher-student dyadic interactions (Jones & Wheatley, 1990;She, 2000). Jones and Wheatley (1990) found that male science teachers asked more direct questions than did female teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences have been found in teacher-student dyadic interactions (Jones & Wheatley, 1990;She, 2000). Jones and Wheatley (1990) found that male science teachers asked more direct questions than did female teachers. She (2000) in her study concluded that teachers' beliefs can influence how they interact with their students.…”
Section: Discussionmentioning
confidence: 99%